The role of ethics, trust, and shared values in the creation of loyalty: empirical evidence from the Moroccan University™ - Nejjari, Zakaria; Aamoum, Hanane (Business, Management and Economics Engineering, 2020)
Purpose – This research discussed ethics, shared values, university image, and trust as factors of student loyalty. This investigation is performed to discover aspects that influence loyalty. Student loyalty factors were previously researched, but the bulk of the research covered only major loyalty factors such as shared values, trust and university image, but overlooked university ethics as a student loyalty determinant.Research methodology – This study is fundamentally a quantitative study using the methodology of survey research. The information is evaluated using AMOS by means of exploratory factor analysis and structural equation modelling (SEM).Findings – The results show how the image of the university, the ethics and the shared values of the graduates positively influence the trust, which affects loyalty.Research limitations – Regarding the limitations of the study which also reconfigure lines of future research, it is important to note, in the first place, the geographical restriction of the population under study to three Moroccan universities.Practical implications – Educational providers can use the findings to know what increase the loyalty and allocate resources to improve the determinants that affect the trust of the students, thus increasing the allegiance of the learners.Originality/Value – This research provides innovative knowledge regarding the maintenance of the university’s relations with its graduates.